Modification of amphipathic non-opioid dynorphin A analogues for rat brain bradykinin receptors. Issue 1 (1st January 2015) - Lee, Yeon Sun; Hall, Sara M.; Ramos-Colon, Cyf; Remesic, Michael; LeBaron, Lindsay; Nguyen, Ann; Rankin, David; Porreca, Frank; Lai, Josephine; Hruby, Victor J.
Graphical abstract